MIRACLES AND THE PERFECTION OF BEING: THE THEOLOGICAL ROOTS OF SCIENTIFIC CONCEPTS - Alexis V. Halapsis (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose of the article is to study the Western worldview as a framework of beliefs in probable supernatural encroachment into the objective reality. Methodology is underpinned with the idea that every cultural-historical community envisions the reality principles according to the beliefs inherent to it which accounts for the formation of the unique “universes of meanings”. The space of history acquires the Non-Euclidean properties that determine the specific cultural attitudes as well as part and parcel mythology of the corresponding communities. Originality consists in the approach to the miracle as a psychological need in a religious authority, expressed through the religious and non-religious (scientific) worldviews, which are interconnected by invariant thinking patterns deeply inside. It has been proven that the full-fledged existence of the religion is impossible without a miraculous constituent. It has been illustrated that the development of society causes a transformation of beliefs in gods and in miracles they do. The theological origins of the scientific beliefs stating the importance and regularity of the natural processes have been outlined. Conclusions. Religion suggests emotional involvement and reasoning which is realized by means of a miracle. The modern science reproduces the theological concept of the permanence of God and His will at own level. Through the history of humankind not only the nature of miracle (whereof the common tendency belongs to the daily reality expansion) underwent changes but also its suggested subject (wherein abstraction is in trend).